Pengaturan Hukum Mengenai Gratifikasi Pelayanan Seksual Dalam Menanggulangi Tindak Pidana Korupsi - Muhammad Alvito Dary; Supanto Supanto; Ismunarno Ismunarno (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This gratuity is a practice that often occurs in a nation, which is carried out by state administrators or state officials. Gratification is one form given to state administrators or state officials to influence the performance of public officials which can create the potential for creating an economy at high costs and can affect the quality and fairness of services provided to the community. In the development of this gratification, initially gratification only took the form of money and goods, but in fact the practice of gratification has developed in the form of sexual services. This research seeks to answer the issue of limits on gratification as regulated in Article 12 B of the Corruption Eradication Law. Because the existence of gratification for sexual services must be regulated first so that the perpetrator can be subject to criminal sanctions. As a comparison for this research, it uses a comparative method by examining legal regulations regarding gratification in another country, namely Singapore.